Associations between urbanization and avian communities in the Afrotropics: evidence from taxonomic, functional and phylogenetic diversity - Awoyemi, A.G.; Barshep, Y.; Manu, S.A.; Ibanez-Alamo, J.D. (Elsevier, 2024)
Urbanization negatively affects biodiversity worldwide, with the rapidly urbanizing Afrotropical area being understudied. Furthermore, most previous studies investigating this topic focused on taxonomic diversity while recent findings have highlighted the need to incorporate complementary diversity metrics. Thus, this study investigated how urbanization affects bird taxonomic, functional, and phylogenetic diversity in Nigeria, a country with one of the fastest rates of urbanization in the world. We conducted bird censuses at 400 points organized across eight paired comparisons (urban vs non-urban habitats), vegetation zones (rainforest vs savannah), and seasons (dry vs wet). Of the total 237 bird species recorded, 65 % were never encountered in urban areas, suggesting the negative effect of urbanization that was also supported by our statistical analyses. Taxonomic diversity was significantly higher in non-urban than urban habitats. This contrasted with the result on functional and phylogenetic diversity, which was higher in the urban than non-urban habitat. These relationships were similar across seasons, but more intense in the rainforest, revealing that birds in this vegetation zone are more vulnerable to urbanization than their savannah counterparts. We also found that water cover significantly promoted all avian diversity metrics analyzed during the dry season independently of urbanization. In contrast, canopy and bush cover mediated the effects of urbanization on some diversity components (i.e., functional and phylogenetic diversity). Our results highlight the significance of incorporating spatiotemporal patterns in related studies and provide much needed information for city planners and other urban stakeholders in the Afrotropics.